Glia Cell Morphology Analysis Using the Fiji GliaMorph Toolkit. Issue 1 (23rd January 2023) - Kugler, Elisabeth; Breitenbach, Eva‐Maria; MacDonald, Ryan
Abstract: Glial cells are the support cells of the nervous system. Glial cells typically have elaborate morphologies that facilitate close contacts with neighboring neurons, synapses, and the vasculature. In the retina, Müller glia (MG) are the principal glial cell type that supports neuronal function by providing a myriad of supportive functions via intricate cell morphologies and precise contacts. Thus, complex glial morphology is critical for glial function, but remains challenging to resolve at a sub‐cellular level or reproducibly quantify in complex tissues. To address this issue, we developed GliaMorph as a Fiji‐based macro toolkit that allows 3D glial cell morphology analysis in the developing and mature retina. As GliaMorph is implemented in a modular fashion, here we present guides to (a) setup of GliaMorph, (b) data understanding in 3D, including z‐axis intensity decay and signal‐to‐noise ratio, (c) pre‐processing data to enhance image quality, (d) performing and examining image segmentation, and (e) 3D quantification of MG features, including apicobasal texture analysis. To allow easier application, GliaMorph tools are supported with graphical user interfaces where appropriate, and example data are publicly available to facilitate adoption. Further, GliaMorph can be modified to meet users' morphological analysis needs for other glial or neuronal shapes. Finally, this article provides users with an in‐depth understanding of data requirements and the workflow of GliaMorph. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Download and installation of GliaMorph components including example data Basic Protocol 2 : Understanding data properties and quality 3D—essential for subsequent analysis and capturing data property issues early Basic Protocol 3 : Pre‐processing AiryScan microscopy data for analysis Alternate Protocol : Pre‐processing confocal microscopy data for analysis Basic Protocol 4 : Segmentation of glial cells Basic Protocol 5 : 3D quantification of glial cell morphology